Menstrual Equity Initiatives at USA Universities: A Multiple Case Study of Common Obstacles and Enabling Factors - Gruer, Caitlin; Goss, Taylor; Schmitt, Margaret L.; Sommer, Marni (Frontiers in Reproductive Health, 2021)
Background: In recent years there has been growing momentum in the USA around addressing issues of “menstrual equity” and “period poverty,” including a proliferation of university-level initiatives seeking to provide access to free menstrual products. This multiple case study examined four such efforts at a diversity of tertiary institutions to identify the factors that facilitated or impeded success. Methods: We conducted a qualitative multiple case study, including a desk review and key informant interviews with student and administrative actors from universities with free menstrual product initiatives. We sought to identify key learning regarding common challenges and obstacles, enabling factors which supported success and sustainability, and practical learning for future initiatives. From the desk review, four schools (n = 4) were purposively selected to represent a range of geographic regions, student population size, and university type. Purposive sampling was used to identify students and administrators engaged in the menstrual equity initiatives on each campus (n = 20; 4–6 per school). Data from the desk review and interviews were analyzed using thematic analysis. Results: Key themes included (1) the critical role of champions, (2) the importance of social and financial support, (3) challenges diffusing menstrual equity from pilot to scale, and (4) recommendations for future initiatives. University initiatives varied greatly in terms of their scope, funding, and implementation strategy. Conclusion: This multiple case study provides valuable insights regarding the facilitating factors and obstacles faced by initiatives providing free menstrual products at universities. To date, these initiatives have proven successful across the four case studies; however, in most cases, the scope of the initiatives was constrained by limited resources and sustainability concerns. Future campus menstrual equity strategies would benefit from cross-institutional learning and dialogue highlighting design and implementation successes and challenges.